The Effect of The Board of Directors, Audit Committee, and Company Size on The Integrity of Financial Statements (Empirical Study on State-Owned Enterpriseslisted on The Indonesia Stock Exchange 2016-2020 Period) - Sri Anah; Rizky Mustika Anggraeni; Abdul Rahmat (DINASTI RESEARCH, 2023)
This study aims to analyze and obtain empirical evidence about the effect of the board of directors, audit committee and company size on financial statements proxied by conservatism. The sample in this study consisted of 20 State-Owned Enterprises (BUMN) in 2016-2020. With the saturated sample method. This study uses Multiple Linear Regression analysis using SPSS to test the Board of Directors, Audit Committee and Company Size on the Integrity of Financial Statements. The results of this study indicate that the Board of Directors has no effect on the Integrity of Financial Statements, while the Audit Committee and Company Size have an effect on the Integrity of Financial Statements.